A Dynamic CiteSpace Analysis of Research on Foreign Language Effect Abroad - Jichen Wu (International Journal of Education and Humanities, 2025)
Research on the foreign language effect—how using a non-native language influences cognition and decision-making—has gained increasing scholarly attention in recent years. However, there is still limited comprehensive mapping of its development trajectory and thematic evolution on a global scale. This study aims to investigate the research trends, knowledge structures, and emerging hotspots in the field of foreign language effects over the past decade. Utilizing CiteSpace visual analysis software, the study analyzes articles indexed in the Web of Science Core Collection from 2013 to 2023. The analysis focuses on the annual publication trends, geographical distribution of research output, co-citation networks, and keyword clustering. Results indicate a general upward trend in the number of publications, despite fluctuations across years. The dominant research themes revolve around moral psychology, reduced emotionality, dishonesty, and decision-making. The United States, Europe, and East Asia appear as major contributors to this field. These findings suggest that while the foreign language effect has become a prominent interdisciplinary topic, its development in China remains comparatively limited. The study underscores the need to strengthen theoretical frameworks, adopt advanced digital tools such as visual analytics, expand interdisciplinary integration, and deepen empirical exploration within the Chinese context. These implications can inform future research directions and policy decisions aimed at enhancing foreign language education and psychological studies in multilingual settings